Correlation Between Power Line Harmonic Radiation and Magnetospheric Line Radiation Over China - Qiang Guo; Jing Wu; Chao Yue; Li Xie (IEEE Access, 2019)
Power line harmonic radiation (PLHR) and magnetospheric line radiation (MLR) are recognized as electromagnetic pollutants in the near-earth space, and their correlation has been a controversial issue. An identification procedure based on short-time discrete Fourier transform and Welch power spectrum estimation was applied to detect 114 PLHR events and 328 MLR events that occurred as DEMETER satellite flew over China from 2008 to 2010. PLHR events feature parallel horizontal lines with a frequency interval of 50/100 Hz in spectrogram, whereas MLR events feature multi-parallel spectral lines with frequency drift as a baseline for possible triggered emissions as well as triggered emissions with no baseline. We statistically compared the temporal and geographical distribution, Kp and Dst indices, and propagation characteristics between PLHR and MLR events. PLHR events showed more obvious variations annually than MLR events, and the former had a close relationship with the development of Chinese power system. Both PLHR and MLR presented similar diurnal and seasonal differences, owing likely to the ionospheric state; moreover, they appeared to have no significant connection with geomagnetic activity level. The geographical distributions of PLHR and MLR differed significantly. PLHR events occurred in the range of (20° N-45° N), whereas MLR events were concentrated in southwestern low-latitude regions of (18° N-28°N). Furthermore, PLHR waves were right-hand circularly polarized, whereas MLR waves were approximately linearly polarized. In summary, MLR is more likely caused by natural radiation that is not directly related to PLHR, whereas PLHR is closely related to terrestrial power systems.